Pemanfaatan Ampas Sagu Untuk Produksi Bioetanol - Hendra, Alfino; Chairul, Chairul; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Sago waste is a lignocellulosic material that can be used as a raw material for making bioethanol. The lignin content in lignocellulose can inhibit the rate of saccharification by blocking access to cellulase enzymes in cellulose. The pretreatment stage is the initial stage of the conversion process of lignocellulose to bioethanol with the aim of reducing lignin levels in lignocellulose. The next steps in the conversion of lignocellulosic material to bioethanol are saccharification and fermentation. In this study, the pretreatment stage was carried out using 10% NaOH solution at a 4 bar pressure reactor and a temperature of 140 oC, while the saccharification and fermentation stages were carried out simultaneously (SSF) with the help of cellulase enzymes and yeast Saccharomyces cerevisiae at temperature conditions of 30 oC and pH 5. The research was carried out by varying the ratio of sago waste with NaOH solution and the time of the pretreatment process. The ratio of sago waste and the solvent used were 1:5, 1:6, and 1:7, while the processing time started from 20 minutes, 30 minutes and 40 minutes.. The results of the initial treatment stage were then continued with SSF for 0 hours, 24 hours, 48 hours, and 72 hours with the highest bioethanol content of 12% at 72 hours. Keyword: Bioethanol, lignocellulose, pretreatment, sago solid waste, SSF